Henslowe-Alleyn Digitisation Project. - Northway, Kara J. (Renaissance and reformation, 2020)
The article offers information on Henslowe-Alleyn Digitisation Project, digital archive, by Grace Ioppolo which displays and preserves 2,200 high-quality, photographed pages of the most important handwritten documents in English theatre history from the time of Shakespeare.